Development and implementation of a theoretical-practical program to standardize the training of Brazilian foot and ankle surgeon - Ferreira, Ricardo Cardenuto; Costa, Marco Túlio (Scientific Journal of the Foot & Ankle, 2019)
Objective: 1) to identify characteristics of the functioning and production of training centers responsible for the training of foot and ankle specialists in Brazil; 2) establish minimum quality criteria to provide adequate professional training of the foot and ankle specialist; 3) create a baseline to endorse the minimum foot and ankle specialist training program; 4) to rank, in terms of qualification and efficiency, the training centers of specialists in the area of ​​foot and ankle. Methods: protocol containing information provided by physicians responsible for 31 accredited national services as centers for training foot and ankle specialists at ABTPé in the 2012-2015 quadrennium. Results: minimum operating and production criteria were established based on the information collected. We identified that: 1) it was possible to establish criteria for a possible standardization in the training programs, both in the theoretical and practical field; 2) the relevant scientific output of the training centers is still low and should be stimulated to increase both quantity and quality; 3) the academic qualification of physicians responsible for training specialists is low; 4) The classification of training centers according to hierarchical quality criteria can be established by objective criteria. Conclusion: Quality goals, with objective and well-defined criteria, could be established allowing standardizing the type of training offered to training specialists distributed throughout the national territory, making it more uniform. The evaluation criteria adopted also allowed to establish a hierarchical classification of training centers in the area of ​​foot and ankle, creating a reference base to qualify the training offered in these institutions.